Employee Retention in Luxury Accommodation Business in Da Nang, Viet Nam - Tin, Pham Quang; Y, Tran Thi Minh; Hieu, Thai Thi; Trang, Huynh Thi Thu (RA Journal Of Applied Research, 2023)
Employee retention, a strategy towards sustainable development of each enterprise, affects greatly its productivity, quality and efficiency. This paper employs primary data collected from questionnaire, both in online and face-to-face forms, of 390 employees working in high-class accommodation system in Da Nang – Viet Nam. Using quantitative analysis techniques of scale testing, exploratory factor analysis, and multivariable regression analysis, we found that there are 9 major factors having positive effects on employee retention in luxury accommodation business system in Da Nang – Viet Nam. These factors, both material and non-material, include, from higher to lower levels: welfare, salary; manager’s support; corporate social responsibility; recognition and reward; working environment; promotion opportunities; training and development; working conditions.